On the composite Bernstein type quadrature formula - Bărbosu, Dan; Miclăuş, Dan (Rev. Anal. Numér. Théor. Approx., 2010)
Considering a given function \(fC[0,1]\), the interval \([0,1]\) is divided in \(m\) equally spaced subintervals \([k-1m,km]\), \(k=1,m\). On each of such type of interval the Bernstein approximation formula is applied and a corresponding Bernstein type quadrature formula is obtained. Making the sum of mentioned quadrature formulas, the composite Bernstein type quadrature formula is obtained.